THE IMPACT OF ENVIRONMENTAL POLLUTION ON THE ENVIRONMENTAL OF FARM ANIMALS (CAHIERS MAGELLANES-NS, 2024)
The study showed that the Iraqi environment is one of the most dangerous environments due to poor central planning, unbalanced population growth, the leakage of polluting materials such as fuel, liquid sulfur, and concentrated acids from industrial facilities, the disruption of electrical energy sources, and the destruction that befell oil refineries as a result of wars and the cessation of work, in addition to the great neglect of the issue of waste collection and recycling. And so on. Therefore, it is necessary to carry out some treatments, including providing adequate lighting. Natural light facilitates vision, encourages work, and helps kill microbes. It also ensures the safety of the roof, walls, and floor of the barns, as it is necessary that the walls be sound and free of cracks and openings that harbor insects. The roof should be made of heat-insulating materials and the floor should be easy to clean. It is also very necessary for this barn to receive the largest amount of warmth from the sun’s rays, in addition to protecting the barn from extremely cold winds in the winter, especially. Choose a typical location for the barn so that it is far from areas Residential barns should be separated from each other to prevent the spread of diseases and epidemics. They should also be built from the side that allows sunlight to enter the interior to provide light in addition to warmth. Barns should be built in a way that opposes the gusts of wind, and it is preferable to create windbreaks, especially in the case of choosing an open barn. They should be The process of storing fodder properly, away from damp places, to prevent it from rotting, in addition to ensuring that the places are clean and not exposed to dirt, such as animal waste itself.